Energy consumption, gross domestic product, foreign direct investment and CO2 emission in Malaysia / Mohd Azim Sardan, Azman Ali, Tan Yan Ling and Abdul Razak Jambari - Sardan, Mohd Azim; Ali, Azman; Tan, Yan Ling; Jambari, Abdul Razak (2012)
This paper aims to study the relationship between energy consumption, gross domestic product (GDP), foreign direct investment (FDI) and CO2 emission in Malaysia. In our study, we used the Vector Error Correction (VEC) framework by initially looking at the long run and short run relationship between these variables via the Johansen cointegration technique. Yearly data during the thirty seven-year period (from 1971 to 2007) has been collected from World Bank and tested. The finding provides evidence for the existence of a longrun relationship between these variables for the period. The result also shows that there is a uni-directional causality from energy consumption to GDP and FDI.